Dual blockade of EGFR and PI3K signaling pathways offers a therapeutic strategy for glioblastoma - Tongxuan Guo; Changyong Wu; Junhao Zhang; Jiefeng Yu; Guoxi Li; Hongyan Jiang; Xu Zhang; Rutong Yu; Xuejiao Liu (Cell Communication and Signaling, 2023)
Abstract Background Glioblastoma multiforme (GBM) is a devastating disease that lacks effective drugs for targeted therapy. Previously, we found that the third-generation epidermal growth factor receptor (EGFR) inhibitor AZD-9291 persistently blocked the activation of the ERK pathway but had no inhibitory effect on the phosphoinositide 3-kinase (PI3K)/Akt pathway. Given that the PI3K inhibitor GDC-0084 is being evaluated in phase I/II clinical trials of GBM treatment, we hypothesized that combined inhibition of the EGFR/ERK and PI3K/Akt pathways may have a synergistic effect in the treatment of GBM. Methods The synergistic effects of cotreatment with AZD-9291 and GDC-0084 were validated using cell viability assays in GBM and primary GBM cell lines. Moreover, the underlying inhibitory mechanisms were assessed through colony formation, EdU proliferation, and cell cycle assays, as well as RNA-seq analyses and western blot. The therapeutic effects of the drug combination on tumor growth and survival were investigated in mice bearing tumors using subcutaneously or intracranially injected LN229 xenografts. Results Combined treatment with AZD-9291 and GDC-0084 synergistically inhibited the proliferation and clonogenic survival, as well as induced cell cycle arrest of GBM cells and primary GBM cells, compared to monotherapy. Moreover, AZD-9291 plus GDC-0084 combination therapy significantly inhibited the growth of subcutaneous tumors and orthotopic brain tumor xenografts, thus prolonging the survival of tumor-bearing mice. More importantly, the combination of AZD-9291 and GDC-0084 simultaneously blocked the activation of the EGFR/MEK/ERK and PI3K/AKT/mTOR signaling pathways, thereby exerting significant antitumor activity. Conclusion Our findings demonstrate that the combined blockade of the EGFR/MEK/ERK and PI3K/AKT/mTOR pathways is more effective against GBM than inhibition of each pathway alone, both in vitro and in vivo. Our results suggest that AZD-9291 combined with GDC-0084 may be considered as a potential treatment strategy in future clinical trials. Video Abstract